Burnout Risks of Filipino College Students during the Covid- 19 Pandemic: A Basis for Institutional Mental Health Program - Ramos, Belinda; Baptista, Gemlee; Fulong, Lorna; Sabaulan, Jose (Technium Social Sciences Journal, 2021)
Student burnout is a concept born out of the occupational syndrome of working adults. In the course of the COVID-19 pandemic and shift of learning from face-to-face to online, people have experienced mental health issues in terms of burnout, especially among college students. With no mental health program in place in many higher education institutions, there is a need to find out students’ burnout risks and status. This study used a modified survey questionnaire from the American Public Welfare Association to determine the burnout risks of the 245 student participants of a university in the northern Philippines. Results showed that the participants have moderate to high risks for burnout, especially the female students. These students already need interventional measures to combat their present mental health problems. It is thus recommended that future researchers be done on burnout that studies the different student constructs of burnout to formulate a more comprehensive mental health program specifically designed for students.